Auditoría operativa a los costos por servicios de seguridad y su incidencia en la rentabilidad de la empresa Conasepri seguridad especial Cía. Ltda. de la ciudad de Quevedo, año 2017 - Posligua Peralta, Verónica Dolores (2018)
The present investigation was developed in the Security Company CONASEPRI SEGURIDAD ESPECIAL CIA. LTDA., Dedicated to provide surveillance services and private security in fixed, mobile and electronic mode in the city of Quevedo, established since 2007. The general problem of the company is: How does the operational audit affect the costs for services of security in the profitability of the company CONASEPRI SEGURIDAD ESPECIAL CÍA. LTDA.?, The problem served to derive the sub-problems that contributed to the analysis of costs for security services provided by the company through the establishment of the following objectives: -Analyze the control performed by the company to the costs for security services; -Examine the application of NIC 19 Benefits to employees of the company; -Analyze the profitability of the financial information presented by the company Conasepri Seguridad Especial Cía. Ltda., Therefore, one was carried out in which the type of analytical, documentary and descriptive research was used to determine the incidence of costs on the profitability of the company. This allowed us to have a clear vision of how the costs are being carried out in the company, what effects the application of NIC 19 has had on employees and the repercussion of these on the profitability of the financial information presented, which allowed its analysis guarantees the continuity of the company in the competitive market. The results obtained will serve as a support tool for the administrative management of the costs for services granted to the different companies allowing to control, organize and optimize the resources used according to the procedures immersed in the controls carried out by the company, in the same ones that were concluded in which the company uses the accounting system for the analysis and presentation of the financial statements in which the costs for employee benefits according to NIC 19 are presented and which reasonably present the profitability, which is analyzed by the executives each accounting period, It was also suggested to improve the controls and procedures to operating costs, with greater emphasis on variable costs and keeping them updated in the accounting system for their respective analysis. In addition, the regulations regarding benefits to employees must be applied and the respective actuarial calculations must be applied. since they are the engine principal of the company to determine whether the company has actuarial gains or losses for making decisions.